Kebiasaan Makanan Ikan Gelodok (Mudskipper) di Perairan Pantai Dumai - Dony Ingot Panjaitan; Syafruddin Nasution; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Mudskipper is included family Gobidae of class Actinopterygii.Geographically, these fish are widespread and abundant in tidal areas andestuaries. This study was conducted in July 2013, located in Sesai Village Dumaicoastal waters. This study aims to determine the type of food consumed byMudskipper, especially those inhabiting coastal waters of Dumai. The methodused in this study is a survey method. Samples obtained from the field and thenanalyzed in the laboratory. Water quality parameters measured includetemperature, salinity, soil pH, water pH, and DO (Dissolved Oxygen). Samples offish used in this study were divided into 3 groups of size, which the size of 0-70mm, 71-140 mm in size and length of 140 mm. From stomach contents analysisshow that mudskipper consume ten types of food that consists of molluscs(Alocinma longicornis and Onicomelania hupensis chiur), crustaceans(Holometopus haematocheir), Fish (Periopthamus and Harpodon neherous),Insecta (Psepenus herricki and Oecophylla smaragdina), Cyanophyceae(Gloetricha echimulata) and Angiosperms (Najas japonica Nakai). From theresults of ANOVA test, there was no significant different between the types offood consumed by fish of different sizes. The value of Relative Important Index(IRP) proves that the main food type of Mudskipper from Dumai coastal waters isHolometopus haematocheir (Crustacea). It can be concluded that the Mudskipperfish are carnivores.Keywords: Food Habits, Mudskipper, Coastal Waters, Dumai